Kimura disease in children: A report of 11 cases and review of the literature - Mai, Yumiao; Wang, Yingjie; Sun, Pan; Jing, Zhaohe; Dong, Pengpeng; Liu, Jian (Frontiers in Pediatrics, 2023)
Introduction Kimura disease (KD), also known as eosinophilic hyperplastic lymphoid granuloma, is a rare benign chronic inflammatory condition, which is featured with the painless progressive mass located in the subcutaneous area of the head and neck region, elevated peripheral blood eosinophils, and raised serum immunoglobulin E (IgE) levels. KD is uncommon in clinical practice, especially with low incidence in children, so it often leads to misdiagnosis or missed diagnosis in pediatric patients. Methods The clinical data of 11 pediatric patients with KD in the authors' institution were retrospectively analyzed. Results There were 11 pediatric patients with KD enrolled in total, including 9 male patients and 2 female patients (sex ratio 4.5:1). The median age at diagnosis stood at 14 years (range 5-18 years), the initial symptoms in all patients included painless subcutaneous masses and focal swelling, the duration of symptoms ranged from 1 month to 10 years, and the average duration was 24.45 months. Six patients had single lesions, and 5 had multiple lesions. The highest proportion of lesion regions were parotid gland (n = 5, 31.3%) and retroauricular (n = 5, 31.3%), followed by cervical lymph nodes (n = 4, 25%), and others (n = 2,12.5; elbow n = 1; back n = 1). The eosinophil absolute count elevated in all patients, ranging from 0.71×109/L to 10.35 ×109/L (normal range 0.02-0.52×109/L). IgE levels were increased in all 7 patients who underwent serum immunoglobulin examination (normal range <100 IU/mL). Three patients received oral corticosteroid treatment while 2 relapsed. Three patients received surgical resection combined with oral corticosteroid treatment, and no patient relapsed. The other 3 patients received surgery and radiotherapy, surgery combined with corticosteroid and cyclosporin and corticosteroid combined with leflunomide respectively, and no patient relapsed. Conclusion Base on the study, it is found that Kimura disease is rare and may have the atypical symptoms in pediatric patients, combination therapy is recommended to reduce recurrence, and long-term follow-up should be performed.